Meningkatkan Kemandirian Keuangan IAIN Parepare dalam Proses Transformasi Manajemen Keuangan Badan Layanan Umum - Hasim (JURNAL ILMIAH GEMA PERENCANA, 2025)
This policy paper describes that the transformation of the State Islamic Institute (IAIN) Parepare into a Public Service Agency (BLU) is a response to national policy aimed at enhancing fiscal independence and service efficiency in religious higher education institutions. However, current conditions reveal that 78.2% of the institution’s budget still relies on state funding (APBN), with limited asset utilization and inadequate human resource capacity in BLU-based financial management. This gap highlights the urgency of a systematic analysis of the challenges and strategic directions in the transition process. This policy study adopts a qualitative approach with a case study design, using document analysis, semi-structured interviews, and descriptive-interpretive analysis. The findings identify four core issues: low non-tax revenue (PNBP), weak performance-based management culture, underutilization of assets, and insufficiently trained financial personnel. Through the USG analysis and the application of the Resource-Based View (RBV), New Public Management (NPM), and revenue diversification frameworks, the establishment of Campus Business Units (UBK) emerges as the most effective and efficient policy alternative. The study concludes that financial autonomy can only be achieved through structured asset governance, incentives for competent personnel, and supportive internal regulations. The key recommendation is for the Rector to issue a regulation mandating the establishment of UBKs at the faculty level to optimize the economic value of institutional assets, particularly buildings and laboratories.